Ethical implications of data mining - Franganillo, Jorge (Anuario ThinkEPI, 2010)
Data mining is the process of analyzing large data sets to discover behaviour patterns and predict future actions. Data mining has many useful applications, but also has an exploratory approach that makes questionable the validity of certain deductions. Using personal information for predictive purposes has a direct impact on the lives of people and therefore requires acting in a framework of liability. A code of ethics is necessary.
Keywords: Data mining; Ethics; Personal information.